Steam Turbine Components

An amorphous carbon film on steam turbine components addresses scale adhesion issues under high temperature and pressure, reducing scale deposition by up to 1/20 and maintaining efficiency, while avoiding corrosion and cost, by using a carbon film with specific Raman spectrum and composition.

JP7602771B2Active Publication Date: 2024-12-19FUJI ELECTRIC CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023184855
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-06
Filing Date
2023-10-27
Publication Date
2024-12-19
Estimated Expiration
2040-12-01

AI Technical Summary

Technical Problem

Existing steam turbine technologies struggle to effectively suppress scale adhesion under high temperature and pressure conditions without causing corrosion or reducing power generation efficiency, and the use of organic materials for scale control is costly and thermally unstable.

Method used

Application of an amorphous carbon deposited film on steam turbine components, specifically designed with a Raman spectrum D band and G band intensity ratio of 0 to 1.5, containing hydrogen and/or nitrogen, and a thickness of 100 nm to 8 μm, to prevent scale adhesion.

Benefits of technology

The carbon deposited film significantly reduces scale adhesion by up to 1/20 compared to conventional methods, preventing operation stoppages and maintaining power generation efficiency without the need for costly solutions or thermal degradation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602771000002
    Figure 0007602771000002
  • Figure 0007602771000003
    Figure 0007602771000003
  • Figure 0007602771000004
    Figure 0007602771000004
Patent Text Reader

Abstract

To provide a steam turbine member that suppresses scale adhesion without impairing the turbine's performance, including its corrosion resistance.SOLUTION: There are provided a steam turbine member having a deposited amorphous carbon film provided in an area on a base material at which scale deposition easily occurs, a steam turbine including the same, and a method for producing the steam turbine member. The deposited carbon film is a deposited carbon film having a relative intensity ratio (Id / Ig) between intensities at a D band and at a G band of a Raman spectrum of 0 to 1.5. The deposited carbon film contains 0 to 40 at% of hydrogen and / or 0 to 30 at% of nitrogen. The deposited carbon film has a thickness of 100 nm to 8 μm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a steam turbine component, and more particularly to a steam turbine in which scale deposition is suppressed. [Background technology]

[0002] In the steam turbines used in geothermal power generation, the thermal energy of high-temperature, high-pressure geothermal steam is converted into rotational force via turbine blades in order to generate electricity. During this process, the steam loses its energy and its temperature and pressure drop. When the temperature and pressure of high-temperature, high-pressure geothermal steam drop, silica, calcium, iron sulfide, and other substances dissolved in the steam precipitate and accumulate on the surface of the turbine blades. As this accumulation progresses, the flow path of the geothermal steam becomes blocked. This is called scaling. Scaling can cause unexpected power plant shutdowns, lower the operating rate of geothermal power plants, and significantly reduce the amount of electricity generated by geothermal power plants. For this reason, scaling is considered an issue that must be resolved.

[0003] It is known that the rate of scale deposition decreases with the pH of geothermal steam, and scaling can be suppressed to some extent by reducing the pH to 5 or less. Specific methods for achieving this include injecting sulfuric acid or hydrochloric acid into the geothermal fluid. The deposition rate of silica, one of the main components of scale, can be reduced as the pH decreases. Similarly, calcium precipitates in the form of calcium carbonate, etc., but this calcium salt dissolves at low pH, making it possible to reduce calcium-containing scale. However, a decrease in the pH of geothermal steam may increase the risk of corrosion damage to the ferrous materials that make up the turbine.

[0004] Another known technology is to reduce the effect of scale accumulation on the blade surface on output reduction by making the nozzle blades and throat width at the turbine inlet side larger than in conventional technology (see Patent Document 1).

[0005] A technology is known that suppresses the adhesion of scale by spraying a solution containing an organic material having a carboxyl group into geothermal steam (see Patent Document 2). This technology solves the problem of corrosion resistance because it does not require the injection of acid. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2003-214113 A [Patent Document 2] JP 2017-160842 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, the technology of Patent Document 1 could not fundamentally suppress the adhesion of scale itself. In addition, the technology of Patent Document 2 has a problem that the power generation efficiency decreases due to the decrease in steam temperature and the increase in wetness caused by spraying a solution into the steam. In addition, the solution containing the organic material needs to be constantly introduced, which increases the cost. Furthermore, the heat resistance temperature of these organic materials is 200°C or less, and in power generation facilities that use geothermal steam that reaches a high temperature of about 220°C, the aforementioned organic materials may thermally decompose, and the expected effect of suppressing the adhesion of scale may not be obtained.

[0008] In response to the above-mentioned problems, there is a need for a steam turbine component that can suppress scaling under high temperatures and pressures without the risk of damaging components that constitute the turbine or restricting operating conditions, and a steam turbine equipped with such a component. [Means for solving the problem]

[0009] According to one embodiment, the present invention relates to a steam turbine component having an amorphous carbon deposited film on a base material.

[0010] In the steam turbine component, the carbon deposition film has a Raman spectrum D band (1360 cm -1 (around 1580cm) and G band (around 1580cm) -1 It is preferable that the carbon deposition film has a relative intensity ratio (Id / Ig) of 0 to 1.5.

[0011] In the steam turbine component, the carbon vapor-deposited film preferably contains 0 to 40 at % hydrogen and / or 0 to 30 at % nitrogen.

[0012] In the steam turbine component, the carbon vapor deposition film preferably has a thickness of 100 nm to 8 μm.

[0013] In the surface portion of the carbon vapor deposition film of the steam turbine component, the graphite content G (%) in the carbon component and the hydrogen content H (at%) are expressed by the following formula (1): H≧1.5118×G-40.603 (1) It is preferable that the relationship expressed by the following formula be satisfied:

[0014] In the steam turbine component, it is preferable that the carbon vapor-deposited film has a maximum height roughness Rz of 6.3 μm or less.

[0015] In the steam turbine component, it is preferable that the carbon vapor deposition film is provided on the base material via an intermediate layer.

[0016] The steam turbine component is preferably a first stage vane.

[0017] According to another embodiment, the present invention relates to a steam turbine including any of the steam turbine components described above.

[0018] According to another embodiment, the present invention relates to a method for manufacturing a steam turbine component having an amorphous carbon vapor deposition film on a base material, the method including the steps of applying a high-energy heat source to a carbon source in a vacuum and depositing a carbon-containing substance generated by the step on the base material.

[0019] The above-mentioned production method preferably further comprises the step of supplying a hydrogen source and / or a nitrogen source and depositing hydrogen and / or nitrogen on the base material together with the carbon. Effect of the Invention

[0020] According to the present invention, it is possible to obtain a steam turbine component in which the amount of scale adhesion is, for example, 1 / 4 or less, and at a minimum, approximately 1 / 50, compared to the conventional technology, a manufacturing method thereof, and a steam turbine equipped with the steam turbine component. [Brief description of the drawings]

[0021] [Figure 1] FIG. 1 is a graph showing the relationship between the nitrogen concentration in the carbon vapor-deposited films and the amount of attached scale in Examples 1(i) to 1(v). [Diagram 2] FIG. 2 is a graph showing the relationship between the hydrogen concentration in the carbon vapor-deposited films and the amount of scale adhesion in Examples 2(i) to 2(iii). [Diagram 3] FIG. 3 is a graph plotting the graphite content G (%) and hydrogen content H (at %) in the surface portion of the carbon vapor-deposited film of Example 3, and showing the relationship between G and H that realizes a low adhesion amount. [Figure 4] FIG. 4 is a conceptual diagram showing the occurrence of scaling in a first stage stator vane of a steam turbine according to the prior art. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. However, the present invention is not limited to the embodiment described below.

[0023] [First embodiment: steam turbine component] According to a first embodiment, the present invention relates to a steam turbine component having an amorphous carbon vapor-deposited film on a base material.

[0024] In the present invention, the steam turbine components refer to various components constituting a steam turbine, including, but not limited to, steam turbine stator blades, steam turbine rotors, bearings, casings, casing seals (seal fins), seals for preventing steam leakage, main steam valves, steam and hot water transport pipes, steam separators, condensers, evaporators, and condenser heat exchangers. In particular, the steam turbine components refer to, but are not limited to, geothermal steam turbine components that come into contact with geothermal steam and may cause scaling problems due to calcium and silica.

[0025] The base material constituting the steam turbine component may generally be a metal, such as stainless steel, which is excellent in corrosion resistance, heat resistance, and wear resistance and is usually used in steam turbines. The base material varies depending on the type of the above-mentioned components and their arrangement in the steam turbine, and may include carbon steel, low alloy steel, martensitic stainless steel, austenitic stainless steel, ferritic stainless steel, etc. In addition, for example, the base material of the steam turbine vane may be 13% Cr steel, and the base material of the seal fin may be 17% Cr steel such as SUS410, but is not limited to these. It is preferable that the surface of the base material corresponding to the portion where the carbon vapor deposition film is formed is mirror-polished.

[0026] The carbon vapor-deposited film may be provided on the entire surface of the base material of the steam turbine component, or on a portion of the base material. Typically, it can be provided partially on a portion of the base material where scale is likely to adhere. The portion of the base material where scale is likely to adhere varies depending on the component, but is generally known in the art. For example, when the steam turbine component is a steam turbine stator blade, particularly a first-stage stator blade, the portion of the base material where scale is likely to adhere is from the top to the edge on the suction side of the profile, and it is preferable to provide a carbon vapor-deposited film at least on this portion. Alternatively, when the steam turbine component is a seal fin, the surface of the seal fin is the portion where scale is likely to adhere.

[0027] As an example of a steam turbine component for which it is particularly desirable to suppress the adhesion of scale, a first-stage stator vane will be further described with reference to the drawings. FIG. 4 is a conceptual diagram showing scaling in a first-stage stator vane of a steam turbine according to the prior art. The first-stage stator vanes 101a and 101b are fixed to a casing (not shown) at a location closest to an inlet of geothermal steam 100 among approximately seven to a dozen stator vanes in a steam turbine, forming a blade row. In addition, a moving blade 102 is provided in close proximity to the stator vanes. After colliding with the first-stage stator vanes 101a and 101b in the direction shown by the arrow in FIG. 4, the geothermal steam 100 flows between the adjacent stator vanes 101a and 101b. At that time, silica and calcium dissolved in the geothermal steam adhere to and precipitate as scale S on the blade surface where the flow velocity of the geothermal steam is the smallest, from the top to the edge of the profile. On the other hand, in the rotor blade 102 located downstream in the direction of geothermal steam flow relative to the stator vanes 101a and 101b, scaling is less likely to occur than in the first stage stator vanes 101a and 101b. Scale S adhering to the first stage stator vanes 101a and 101b can block the steam flow path and cause operation to stop. In the present invention, scaling can be effectively prevented by providing a carbon vapor deposition film in the area corresponding to the scale S shown in Figure 4.

[0028] Next, the amorphous carbon vapor deposition film will be described in detail. The amorphous carbon vapor deposition film is a film that contains amorphous carbon as a main component and is produced by a vapor deposition method. In the present invention, containing carbon as a main component means that the total mass of the film contains carbon at 50% or more. The amorphous carbon vapor deposition film may typically be a diamond-like carbon (DLC) film, and may be a chemical vapor deposition film or a physical vapor deposition film. The amorphous carbon vapor deposition film has a D band (1360 cm) in the Raman spectrum. -1 (around 1580cm) and G band (around 1580cm) -1The relative intensity ratio (Id / Ig) of the carbon vapor deposition film (near the surface of the carbon vapor deposition film) is preferably 0 to 1.5, and more preferably about 0.3 to 1.0. In particular, when the carbon vapor deposition film is a chemical vapor deposition film, the preferred Id / Ig is, for example, 0.0 to 1.0, and when the carbon vapor deposition film is a physical vapor deposition film, the preferred Id / Ig is, for example, 0.0 to 1.2. It is believed that Id / Ig correlates with the ratio of Sp2 structure to Sp3 structure in the carbon vapor deposition film having an amorphous structure. In the present invention, when Id / Ig is within the above range, it is particularly effective in preventing scaling.

[0029] The carbon deposition film may be a deposition film composed substantially of carbon alone. In this case, too, elements that are unavoidable in the manufacturing process may be included. A deposition film composed of carbon alone has the advantages of significantly suppressing scaling, being highly hard, and being highly wear-resistant, as compared to a base material not provided with such a film.

[0030] The carbon deposition film may be a deposition film containing hydrogen and / or nitrogen. The hydrogen content in the carbon deposition film is preferably more than 0 and about 40 at% (atomic %) or less, and more preferably 10 at% or more and about 40 at% or less. When the carbon deposition film contains hydrogen in such a range, scale adhesion can be effectively prevented. The nitrogen content in the carbon deposition film is preferably more than 0 and about 30 at% or less, and more preferably more than 0 and about 16 at% or less. When the carbon deposition film contains nitrogen in such a range, scale adhesion can be effectively prevented. The carbon deposition film may contain both hydrogen and nitrogen. In this case, the total content of hydrogen and nitrogen may be about 40 to 60 at%, but is not particularly limited.

[0031] Regardless of whether or not hydrogen and / or nitrogen is contained, the carbon deposition film according to the present invention may contain a trace amount of oxygen due to the manufacturing method. Also, the carbon deposition film may contain nonmetallic elements such as silicon (Si) due to the intermediate layer described below.

[0032] The thickness of the amorphous carbon deposition film may be uniform throughout the member or may vary depending on the site. Also, although the thickness of the carbon deposition film is not particularly limited, it is preferably 100 nm to 8 μm, and more preferably 1 to 6 μm.

[0033] Since the surface of the amorphous carbon deposition film is relatively smooth, the surface roughness of the carbon deposition film also varies depending on the roughness of the base material on which the carbon deposition film is formed. Therefore, a desired surface roughness can be achieved depending on the material selection of the base material and the degree of surface polishing. In one embodiment, the surface roughness of the carbon deposition film preferably has a maximum height roughness Rz of 6.3 μm or less. The maximum height roughness Rz refers to a value measured using a stylus type surface roughness measuring device.

[0034] In the surface portion of the amorphous carbon deposition film, it is preferable that the amount of graphite G (%) in the carbon component and the hydrogen content H (at%) satisfy the relationship represented by the following formula (1). H≧1.5118×G - 40.603 (1) However, 0≦H≦60 and 0 < G. When the hydrogen content H in the carbon deposition film exceeds 60 at%, it exhibits plastic properties instead of diamond-like carbon. Therefore, H is preferably 60 at% or less.

[0035] Here, the surface part of the carbon deposition film refers to the part within about 2 nm from the outermost surface of the carbon deposition film. The graphite content G(%) in the carbon component refers to the percentage of the number of graphite atoms with respect to the total number of carbon atoms constituting the surface part of the carbon deposition film. More specifically, it refers to the percentage of the number of graphite atoms (mass) with respect to the total number of atoms (total mass) of diamond and graphite contained in the carbon component constituting the surface part of the carbon deposition film. The graphite content G(%) at the surface part can be obtained by X-ray absorption fine structure (XAFS) analysis. On the other hand, the hydrogen content H(at%) refers to the percentage of the number of hydrogen atoms with respect to the total number of atoms constituting the surface part of the carbon deposition film. The hydrogen content H(at%) at the surface part can be obtained by XAFS analysis and / or Elastic Recoil Detection Analysis (ERDA).

[0036] The above formula will be described in more detail with reference to FIG. 3. FIG. 3 is a plot of the composition at the surface part of the carbon deposition film of the examples described later, with G on the horizontal axis and H on the vertical axis. In the graph, the straight line indicated by the broken line represents H = 1.5118×G - 40.603 (0 ≦ H ≦ 60). When G and H at the surface part of the carbon deposition film satisfy the relationship where 0 < G, 0 ≦ H ≦ 60, and they are on or to the left of the broken line, the scale adhesion amount can be extremely reduced. More specifically, the carbon deposition film can have a scale adhesion amount of about 1 / 20 or less compared to the steam turbine member without the carbon deposition film. In one aspect, for example, from the perspective of production management, etc., it is preferable that H at the surface part is in the range of 10 to 60 at%, preferably 20 to 50 at%, and the composition of the surface part is such that G(%) satisfies formula (1) for H within this range.

[0037] The carbon vapor-deposited film may further contain nitrogen in the surface portion, and may also contain trace components such as oxygen and silicon, so long as H and G satisfy the relationship of formula (1). By including nitrogen in the carbon vapor-deposited film, the amount of graphite in the surface portion can be adjusted, and in particular the amount of graphite can be reduced, thereby obtaining a steam turbine component that can significantly reduce the amount of scale adhesion.

[0038] The amorphous carbon deposition film may be formed in contact with the surface of the base material, or may be formed via an intermediate layer provided on the surface of the base material. The intermediate layer may be a material that improves the adhesion between the base material and the carbon deposition film, and may be a layer containing ceramics or metal. For example, it may be a metal compound containing a metal nitride such as chromium mononitride (CrN) or a metal oxide such as titanium dioxide (TiO2), a silicon compound such as silicon nitride (SiC), or silicon alone, but is not limited thereto. The intermediate layer may be a single layer made of one type of compound, or may be two or more layers made of different compounds. The thickness of the intermediate layer is not particularly limited, and can be appropriately determined by a person skilled in the art.

[0039] The steam turbine component having such a carbon deposition film constitutes a steam turbine together with other components, and is used in power generation facilities, particularly geothermal power generation facilities. As an example, the steam turbine may include a bearing portion fixed on a base, a steam turbine rotor rotatably supported by the bearing portion, and a casing that covers the steam turbine rotor. The outer circumferential surface of the casing is provided with a steam inlet and a steam outlet through which steam is supplied from a geothermal steam well, and the steam turbine rotor may have a configuration in which a plurality of moving blades are fixedly arranged between the steam inlet and the steam outlet in the casing at a predetermined interval in the axial direction, and stationary blades corresponding to these moving blades are fixed to the casing, and these stationary blades and moving blades are arranged alternately in the axial direction. The casing and the rotor may also have seal fins arranged in the axial direction facing the tips of the moving blades and stationary blades, respectively. The condenser connected to the steam outlet of the casing has a nozzle that sprays cooling water, and cools and condenses the steam after use in the turbine. In a geothermal binary power generation system, the condenser has a heat exchanger that cools and condenses the working medium after use in the turbine. One or more of the components constituting such a steam turbine can be provided with a carbon vapor deposition film according to the present invention, thereby making it possible to prevent operation stoppages and reductions in power generation efficiency due to scaling.

[0040] Next, the steam turbine component according to the present invention will be described from the viewpoint of a manufacturing method thereof. The manufacturing method of the steam turbine component according to the present invention, which includes an amorphous carbon vapor-deposited film on a base material, includes the following steps. (1) subjecting a carbon source to a high energy heat source in a vacuum; (2) A process of depositing the carbon-containing substance generated in the above process on a base material to form an amorphous carbon vapor deposition film.

[0041] The method for producing the steam turbine component can be carried out by forming a carbon vapor deposition film on a base material by a dry plating method, and can include the above steps 1 and 2. Such methods include chemical vapor deposition (CVD) using a hydrocarbon gas as the carbon source, and physical vapor deposition (PVD) using solid carbon as the carbon source, and either method can be used to produce the steam turbine component according to the present invention. An example of the chemical vapor deposition method is plasma CVD, and an example of the physical vapor deposition method is evaporation, ion plating, and sputtering, but they are not limited to these.

[0042] In carrying out the manufacturing method, a base material processed into the shape of a predetermined member is prepared. The type of base metal is as described above. Before carrying out the above steps 1 and 2, a step of mirror-polishing the surface of the base material on which the carbon vapor deposition film is to be formed may be included. Alternatively, a step of providing an intermediate layer on the surface of the base material on which the carbon vapor deposition film is to be formed may be included. The intermediate layer can be formed by chemical vapor deposition or physical vapor deposition, similar to the formation of the carbon vapor deposition film. In addition to the above steps 1 and 2, the method may include a step of supplying a hydrogen source and / or a nitrogen source and depositing hydrogen and / or nitrogen on the base material together with the carbon.

[0043] As a first embodiment of the manufacturing method, a manufacturing method using a chemical vapor deposition method, in particular a DC pulse plasma CVD method, will be described. The plasma CVD method can be carried out mainly by an apparatus equipped with a means for introducing a hydrocarbon gas serving as a carbon source into a vacuum chamber, a means for applying a DC pulse bias to a member to be coated, and a means for supporting a base material. As the hydrocarbon gas, methane, ethane, acetylene, etc. can be used, and such a hydrocarbon gas can be selected by a person skilled in the art to suit the purpose.

[0044] In the DC pulse plasma CVD method, in the first step, a DC pulse bias with a negative potential is applied to the turbine material with respect to the grounded film formation container to generate plasma around the base material, and a hydrocarbon gas, for example, methane, is introduced into the plasma generation region. This causes methane to be decomposed by the plasma, and a carbon deposition film containing hydrogen is formed on the base material, and the second step can be performed. During this film formation, the collision energy of the decomposed methane can be changed by controlling the negative voltage applied to the base material, and the decomposition degree of methane can be controlled to control the hydrogen content in the carbon deposition film. Specific conditions for achieving a predetermined hydrogen content in the carbon deposition film can be appropriately determined by a person skilled in the art based on a prior experiment or the like. In the plasma CVD method, a carbon source and a hydrogen source are supplied simultaneously, and a carbon deposition film containing hydrogen can be produced. Note that the chemical deposition method is not limited to the plasma CVD method, and a carbon chemical deposition film can be produced in the same manner when other chemical deposition methods are used.

[0045] Chemical vapor deposition methods such as plasma CVD are particularly advantageous for producing carbon vapor deposition films containing hydrogen. In addition, because a hydrocarbon gas is used as the carbon source, the carbon-containing substance deposited in the second step easily permeates each part of the base material surface, making it easy to form a film on any part of the base material.

[0046] Next, a physical vapor deposition method can be mentioned as a second embodiment of the manufacturing method. The physical vapor deposition method can be mainly performed by an apparatus equipped with a target such as solid carbon, a means for generating a high-energy heat source, and a means for supporting a base material in a vacuum chamber. In the arc ion plating method, which is an example of the physical vapor deposition method, in the first step, a target serving as a carbon source is used as a cathode (negative electrode) and a vacuum arc discharge is generated between the cathode and an anode (positive electrode) to evaporate carbon particles from the target surface. The carbon particles are passed through plasma to give a positive charge, and in the second step, the positively charged carbon particles are deposited on a base material to which a negative bias voltage is applied, thereby forming a carbon deposition film. In addition, a nitrogen ion beam is introduced at the same time as the particles are deposited on the base material, thereby forming a carbon physical vapor deposition film containing nitrogen. The nitrogen content in the carbon deposition film can be controlled by changing the amount of nitrogen gas introduced at this time. A carbon physical vapor deposition film containing hydrogen can also be formed in the same manner by using hydrogen gas instead of nitrogen gas. The physical vapor deposition method is not limited to the arc ion plating method, and a carbon physical vapor deposition film can be produced similarly when other physical vapor deposition methods are used. In the physical vapor deposition method, it is preferable to provide a means for movably supporting the base material in order to deposit carbon particles, which are difficult to reach the desired location compared to hydrocarbon gas depending on the shape and specifications of the base material.

[0047] The physical vapor deposition method is particularly advantageous for producing carbon vapor deposition films containing nitrogen, and is also used for producing carbon vapor deposition films containing both nitrogen and hydrogen. In this case, hydrogen gas is used as the hydrogen source, and the film can be produced by introducing both nitrogen gas and hydrogen gas into a vacuum chamber. Another advantage of the physical vapor deposition method is that it is possible to produce carbon vapor deposition films with a desired composition.

[0048] The composition of the surface portion is a laminate of radicals formed by decomposing methane, which can be used as a source gas in the plasma CVD method, into plasma. Therefore, there is no correlation between the hydrogen content of the entire carbon deposition film and the composition of the surface portion. In order to obtain a composition that satisfies formula (1), it is preferable to form the film by the plasma CVD method and use methane as the source gas. By changing the plasma application conditions, it is possible to adjust the hydrogen content H (at%) that satisfies formula (1) and the graphite amount G (%) in the carbon component at the surface portion.

[0049] The steam turbine component made of the base material having the carbon vapor deposition film formed at desired locations produced as described above can be further combined with other turbine components to produce a steam turbine.

[0050] Furthermore, the method of manufacturing a steam turbine component according to this embodiment includes not only a method for manufacturing a new steam turbine component, but also a method for repairing a steam turbine component. In this case, if necessary, a polishing process or the like may be performed on a part of the surface of the base material, and then a carbon vapor deposition film may be formed on the necessary parts in the same manner as in the manufacturing method of this embodiment, thereby repairing and manufacturing the steam turbine component. EXAMPLES

[0051] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples.

[0052] [Example 1] An amorphous carbon physically vapor deposited film was formed on a base material by physical vapor deposition, and its characteristics were evaluated. A turbine base material made of martensitic stainless steel (SUS420J1) with a diameter of φ22.5 mm and a thickness of 4 mm was used as the base material. In this example, no intermediate layer was provided, and the surface of the base material was mirror-polished, and a carbon vapor deposited film (DLC) was formed directly on the base material.

[0053] The deposition equipment used was a filtered arc position method. The target graphite was placed on the cathode, and a discharge phenomenon was generated at the cathode to evaporate and ionize the graphite, and the ions were then transported to the substrate by a magnetic field to deposit the DLC. The specific equipment configuration used was T-FAD (see, for example, J. Vac. Soc. Jpn. Vol. 51, No.1, Pages 20-25, 2008). The deposition conditions were a back pressure of 4×10 -3 The conditions were: pressure, arc current, 50A, bias, -30V. Before deposition, the turbine base material, which was the material to be deposited, was cleaned for 10 minutes using argon sputtering. N2 gas was introduced as an ion beam into the deposition chamber. DLC films with different nitrogen contents were deposited by introducing nitrogen gas at 0, 5, 10, 15, and 20sccm.

[0054] Using the above method, samples of steam turbine components were fabricated in which a carbon deposition film having a nitrogen content of 0% (Example 1(i)), 5 at% (Example 1(ii)), 12 at% (Example 1(iii)), 16 at% (Example 1(iv)), or 20 at% (Example 1(v)) was provided on a base material to a thickness of 200 to 300 μm. A sample of a base material without a carbon deposition film (comparative example) was also prepared.

[0055] For the samples of Examples 1(i) and 1(v), the Raman scattering light spectrum for 532 nm laser light was measured using a Raman spectrometer, and the Id / Ig of the carbon vapor deposition film was obtained by performing spectral fitting. As a result, Id / Ig was about 0.3 in Example 1(i), about 0.4 in Example 1(ii), about 0.6 in Example 1(iii), about 0.9 in Example 1(iv), and about 1.0 in Example 1(v). In addition, the maximum height roughness Rz of the surface of these carbon vapor deposition films was less than 6.3 μm in all cases.

[0056] In order to verify the effect of inhibiting adhesion of scale, silica, which is the most problematic type of scale, was evaluated, and adhesion tests were performed on the samples of Examples 1(i) to 1(v) and the Comparative Example. Geothermal steam was simulated, and silicic acid, which is the source of silica precipitation, was dissolved in a solution containing NaCl contained in geothermal steam to a supersaturated state. The pH of this solution was adjusted using hydrochloric acid so that the pH would be such that silica would be easily precipitated. The specific composition of the test solution was 200 mmol / l NaCl, 40 mmol / l NaSiO3, and HCl, and the pH was adjusted to 8.5. The samples of Examples 1(i) to 1(v) and the Comparative Example were immersed in this solution and kept at 50°C for three days. Silica was precipitated in a gel state by the immersion treatment. Next, the gel-like silica was removed from the test solution, and the remaining solution was kept at 50°C for one week and dried. Silica was adhered to the surface of the turbine material sample by this heat-retaining and drying treatment. Next, to evaluate the strongly adhered silica, the surface of the turbine material sample was washed with running water and the amount of remaining silica was evaluated by energy dispersive X-ray analysis (EDX). The amount of adhered silica was calculated from the detection intensity of silicon (Si), a constituent element of silica, and the increase in Si amount Δwt% was calculated from the difference in the amount of Si detected before and after the silica adhesion test.

[0057] FIG. 1 is a graph showing the relationship between the nitrogen concentration in the carbon vapor deposition film of Examples 1(i) to 1(v) and the amount of scale adhesion (amount of Si increase measured by EDX). The graph also shows the amount of Si increase in the comparative example sample in which no carbon vapor deposition film was formed as "turbine material". The results in FIG. 1 show that in all of the samples of Examples 1(i) to 1(v), the amount of silica adhesion could be significantly reduced compared to the comparative example sample. Furthermore, by incorporating nitrogen in the carbon vapor deposition film, the amount of silica adhesion could be further reduced.

[0058] In addition, the samples were photographed after the warm drying process and after washing with running water to compare their appearances (photos are not shown). As a result, the uncoated sample was found to have silica attached and coated over the entire surface, while the DLC coated sample only had localized silica attachment. It was also confirmed that the amount of silica attached was reduced in DLC with a high nitrogen content compared to DLC with a low nitrogen content. In particular, the amount of silica attached was reduced most in DLC with a nitrogen content of 15 at%. Furthermore, even when silica was attached to the DLC, cracks and peeling of the silica were observed by SEM observation, and it was confirmed that the adhesion was very weak. On the other hand, the uncoated sample had a thick deposit of silica, and no cracks or peeling of the attached silica was observed.

[0059] [Example 2] A chemical vapor deposition film of amorphous carbon was formed on a base material by plasma CVD, and its characteristics were evaluated. The base material was the same as in Example 1, and the surface was mirror-polished in the same manner as in Example 1, and a carbon vapor deposition film was formed without providing an intermediate layer.

[0060] The deposition equipment used was the DC pulse plasma CVD method (see, for example, Thin Film Manufacturing and Tribology by Plasma Ion Processing, Journal of the Japan Society for Precision Engineering, Vol. 83, No. 4, 2017, p. 319-324). DC pulses were used to generate Ar plasma around the material to be deposited, and when methane gas was introduced as a carbon source, the methane gas was decomposed by the plasma and a film was formed on the material as DLC. The deposition conditions were a chamber pressure of 40 Pa, and prior to deposition, the turbine base material, which was the material to be deposited, was cleaned by argon sputtering. To create an intermediate layer between the DLC and the material being deposited, 6 sccm of Ar, 30 sccm of CH4, and 2 sccm of TMS (tetramethylsilane) were introduced, a bias of -600 V was applied, and the deposition time was set to 2 min to create a silicon-rich intermediate layer. After that, 12 sccm of Ar and 60 sccm of CH4 were introduced, and the bias of the material being deposited was changed to -400, -500, and -700 V to deposit DLC films with different hydrogen contents.

[0061] Using the above method, samples of steam turbine components were produced in which a carbon deposition film having a hydrogen content of 25 at% (Example 2(i)), 32 at% (Example 2(ii)), or 40 at% (Example 2(iii)) was provided on a base material. In addition, a sample of a base material not provided with a carbon deposition film (comparative example) was prepared in the same manner as described in Example 1.

[0062] The Id / Ig of the carbon vapor deposition film of the sample of Example 2 was measured by a Raman spectrometer. As a result, Id / Ig was about 0.54 in Example 2(i), about 0.42 in Example 2(ii), and about 0.28 in Example 2(iii). In addition, the maximum height roughness Rz of the surface of these carbon vapor deposition films was less than 6.3 μm in all cases.

[0063] The scale adhesion suppression effect was verified in the same manner as in Example 1. In Example 2, the amount of silica adhesion was calculated from the detection intensity of oxygen (O), which is a constituent element of silica, and the increase in O Δwt % was calculated from the difference in the detected amount of O before and after silica adhesion.

[0064] FIG. 2 is a graph showing the relationship between the hydrogen concentration in the carbon vapor deposition film of Examples 2(i) to 2(iii) and the amount of scale adhesion (increased amount of O measured by EDX). In the graph, the increased amount of O in the comparative example sample in which no carbon vapor deposition film was formed is also shown as "turbine material". From the results in FIG. 2, in all of the samples of Examples 2(i) to 2(iii), the amount of silica adhesion could be suppressed to a greater extent than in the comparative example sample. Furthermore, by incorporating hydrogen in the carbon vapor deposition film, the amount of silica adhesion could be further reduced.

[0065] [Example 3] Samples of steam turbine components were produced in which a nitrogen-containing carbon vapor-deposited film was provided on a base material in the same manner as in Example 1, and a hydrogen-containing carbon vapor-deposited film was provided on a base material in the same manner as in Example 2. The nitrogen-containing carbon vapor-deposited films were produced so that the nitrogen content in the entire carbon vapor-deposited film was 30.8 at% (Example 3(i)), 32.0 at% (Example 3(ii)), and 34.8 at% (Example 3(iii)). The hydrogen-containing carbon vapor-deposited films were produced so that the hydrogen content in the entire carbon vapor-deposited film was 81.3 at% (Example 3(iv)), 77.7 at% (Example 3(v)), and 77.7 at% (Example 3(vi)).

[0066] In the same manner as in Examples 1 and 2, the effect of inhibiting adhesion of scale was verified for each sample of Example 3. In addition, before the scale adhesion experiment, the composition of the surface portion (within 2 nm from the surface) of the carbon deposition film of Examples 3(i) to 3(vi) was measured. The amount of graphite G (%) in the surface portion was analyzed by XAFS analysis. The hydrogen content H (at%) was measured by ERDA analysis. The nitrogen content was analyzed by X-ray photoelectron spectroscopy. FIG. 3 is a graph plotting the relationship between H and G in the surface portion of the carbon deposition film of Examples 3(i) to 3(vi). The composition of the surface portion and the amount of silica adhesion of each sample of Example 3 are shown in Table 1 below. The amount of silica adhesion is a value when the amount of silica adhesion is set to 1 for a conventional turbine material not formed with a carbon deposition film.

[0067] [Table 1]

[0068] In geothermal power plants where scaling is severe, the steam turbine has traditionally been shut down due to scaling about one year after the start of operation. On the other hand, there is a demand for operation without shutdown for four years or more. The design life of a steam turbine is 20 years, and it is most desirable to be able to suppress scaling for 20 years. Therefore, the effect of reducing adhesion of scale is preferably 1 / 4 or less of the current level, and most desirably 1 / 20 or less. In contrast, in Example 1, the turbine material on which a carbon deposition film with a nitrogen content of 0 to 20 at% is formed was able to reduce the amount of silica adhesion to 1 / 4 or less, as shown in FIG. 1, compared to the conventional turbine material without the carbon deposition film. In addition, it was confirmed that the turbine material on which a carbon deposition film with a nitrogen content of 16 at% was formed, which was particularly effective, was able to reduce the amount of silica adhesion to 1 / 20 or less. In addition, in Example 2, the turbine material on which a carbon deposition film with a hydrogen content of 40 at% is formed was able to reduce the amount of silica adhesion to 1 / 4 or less. Furthermore, by making the surface composition satisfy the relation between the graphite content G (%) and the hydrogen content H (at%) as demonstrated in Example 3, the amount of silica adhesion could be reduced to 1 / 40 or less at most.

[0069] It was confirmed that this embodiment makes it possible to manufacture steam turbine components in which scale adhesion is suppressed, without spraying a solution, which reduces power generation efficiency and increases costs. [Explanation of symbols]

[0070] 101a, b First stage stationary blade, 102 Moving blade 100 Geothermal steam, S scale

Claims

1. A steam turbine component having an amorphous carbon vapor-deposited film on a base material, In the surface portion of the carbon vapor-deposited film, the graphite content G (%) in the carbon component and the hydrogen content H (at %) are expressed by the following formula (1): H≧1.5118×G−40.603 (1) A steam turbine component that satisfies the relationship shown in

2. A steam turbine component as described in claim 1, wherein the carbon vapor deposition film has a relative intensity ratio (Id / Ig) of the D band to the G band in a Raman spectrum of 0 to 1.

5.

3. A steam turbine component as described in claim 1 or 2, wherein the carbon vapor deposition film has a thickness of 100 nm to 8 μm.

4. A steam turbine blade as described in any one of claims 1 to 3, wherein the maximum height roughness Rz of the carbon vapor deposition film is 6.3 μm or less.

5. A steam turbine component according to claim 1, wherein the carbon vapor deposition film is provided on the base material via an intermediate layer.

6. A steam turbine component as described in any one of claims 1 to 5, wherein the steam turbine component is a first stage stator vane.

7. A steam turbine comprising a steam turbine component according to any one of claims 1 to 6.

8. A process comprising the steps of: providing a high energy heat source to a carbon source in a vacuum; depositing the carbon-containing material generated by the above process on a base material; The method for manufacturing a steam turbine component according to claim 1 , comprising:

9. The manufacturing method described in claim 8, further comprising the step of supplying a hydrogen source and / or a nitrogen source and depositing the hydrogen and / or nitrogen on the base material together with the carbon.

Citation Information

Patent Citations

  • Wear resistant hard carbon coating

    JP1999092935A

  • Geothermal turbine

    JP2003214113A

  • Rotary machine with surface smoothening film

    JP2007162613A

  • Scale suppression method and scale suppression device

    JP2017160842A

  • Hard coating and method for manufacturing the same

    JP2019007059A